Highway Politics in a Divided Government Evidence from Mexico - Selod, Harris (The World Bank, 2019)
This paper combines local election results and geo-referenced road construction data over 1993-2012 to investigate political bias in road infrastructure investment in a democratic setting, focusing on the case of Mexico. Using a regression discontinuity design, the paper finds strong evidence of partisan allocation of federally-funded highways to municipalities that voted for the president's party in legislative races, nearly doubling the stock of highways compared to opposition municipalities. The extent of political favoritism in highway provision is stronger under divided government when the president has no majority in the legislature, suggesting political efforts to control the Congress